THE INFLUENCE OF SIMULATION LEARNING STRATEGIES AND LEARNING INDEPENDENCE ON THE OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION LEARNING SCHOOL STUDENTS AT STATE 1 LUBUK PAKAM - Candra Wijaya; Rusydi Ananda; Joko Sulistiono (Universitas Dharmawangsa Medan, 2020)
The objectives of this quasi experimental research were to discover applying whether: (1) the learning achievement of students’ Islamic eduction taught by applying simulation instructional strategy were higher than students’ learning achievement in Islamic education taught by applying expository instructional strategy, (2) the learning achievement of students’ Islamic education with high learning student independent than the learning achievement of students’ Islamic education with low learning student independent, and (3) there was are an interaction between instructional strategy and learning student independentin affecting the learning achievement of students’ Islamic education. The Research findings releaved that: (1) on average the students’ learning achievement taught by applying simulation instructional strategy = 28.12 higher than the average students’ learning achievement taught by applying expository learning strategy = 27.00 with Fcount = 113.96 > Ftable = 3.984, (2) on average the students’ learning achievement with high learning student independent was = 29.61 higher than the learning learning student independent with low = 25.93 with Fcount = 7.66 > Ftable = 3.984, and (3) there was an interaction between instructional strategy and learning learning student independent toward learning achievement in Islamic education with Fcount = 35.48 > F table = 3.984.